PLANNING TO ACCOUNTABILITY: INTEGRATION OF STRATEGIC PLAN, BALANCED SCORECARD AND GOOD GOVERNANCE IN THE GOVERNANCE OF THE NURUL QUR'AN FOUNDATION - Mohammad Abdul Aziz Al Wahedi; Hefniy Hefniy (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
In the era of globalization and increasingly stringent demands for transparency, Islamic educational institutions such as the Nurul Qur'an Foundation face challenges in realizing effective, accountable governance that is oriented towards improving the quality of education. These challenges include the integration of long-term strategic planning, performance measurement systems, and the application of good governance principles. This study aims to analyze in depth how the integration of the Strategic Plan (Renstra), the Balanced Scorecard (BSC), and Good Governance principles is applied in the governance of the Nurul Qur'an Foundation. The research approach used is a qualitative case study method. Data were collected through in-depth interviews with foundation administrators, participatory observation of managerial processes, and a review of the 2021–2025 Renstra document. Data analysis was conducted thematically by highlighting the relationship between strategic vision, performance indicators, and accountability mechanisms. The results show that the integration of Renstra, BSC, and Good Governance creates a more adaptive and transparent governance system, and is able to improve the effectiveness of planning and institutional accountability. This integrative model also has the potential to be applied in other Islamic educational foundations to strengthen institutional competitiveness and organizational sustainability.